DISRUPSI FINANSIAL DIGITAL DAN KETAHANAN KELUARGA: REKONSTRUKSI HUKUM KELUARGA ISLAM TERHADAP PINJAMAN ONLINE BERBASIS MAQASHID SYARI’AH - Wirna; Akbarizan (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This article aims to analyze the impact of online lending on family resilience from the perspective of the maqashid al-shari’ah and to formulate a reconstruction of Islamic family law that is responsive to digital financial disruption. This study employs a qualitative approach with a normative analysis through a literature review of Islamic legal texts, fintech regulations, and relevant scholarly works. The findings indicate that interest-based online lending practices have the potential to undermine the protection of wealth (hifzh al-maal), life (hifzh al-nafs), intellect (hifzh al-‘aql), and lineage (hifzh al-nasl), as they can trigger debt traps, psychological stress, domestic conflicts, and disruptions in meeting children’s needs. Therefore, a reconstruction of Islamic family law is necessary through the reinterpretation of maintenance and family protection, the integration of maqashid al-shari’ah into fintech regulations, and the strengthening of Islamic digital literacy and sharia-compliant financing alternatives.